Dirty Float, Commodity Prices, and Macroeconomic Fluctuations: A Model for Peru - Mendoza, Waldo (2024)
This paper presents a macroeconomic model that replicates the key stylized facts of the Peruvian economy, namely the strong dependence of private investment and GDP on mineral export prices, within a framework where the Central Reserve Bank of Peru (BCRP) operates under a dirty float regime and the Ministry of Economy and Finance (MEF) follows fiscal rules that endogenize public spending. The model is designed for undergraduate students and instructors of economics and builds on the work of Dancourt (2009), Dancourt Mendoza (2016), and Mendoza (2019).